A step-by-step guide to implementing a multidisciplinary endocarditis team. (December 2021) - El-Dalati, Sami; Cronin, Daniel; Riddell, James; Shea, Michael; Weinberg, Richard L.; Stoneman, Emily; Patel, Twisha; Ressler, Kirra; Deeb, George Michael
Over the last several years multiple studies, primarily from European centers have demonstrated the clinical and outcomes benefits of multidisciplinary endocarditis teams. Despite this literature, adoption of this approach to patient care has been slower in the United States. While there is literature outlining the optimal composition of an endocarditis team, there is little information to guide providers as they attempt to transform practice from a fragmented, disjointed process to an efficient, collaborative care model. In this review, the authors will outline the steps they took to create and implement a successful multidisciplinary endocarditis team at the University of Michigan. In conjunction with existing data, this piece can be used as a resource for clinicians seeking to improve the care of patients with endocarditis at their institutions.